Supporting localized interactions using named data networking - Calderon Jaramillo, Andres, author; Papadopoulos, Christos, advisor; Bohm, Wim, committee member; Hayne, Stephen, committee member (Colorado State University. Libraries, 2017)
A common application in the Internet of Things (IoT) is the access to devices in a specific location. For example, a user may walk into a room and use a mobile device to control the lights or to access the temperature reading. Similarly, things in a location need to advertise their services. For example, when a printer is moved into a room, it needs to make its presence known so that users in that room can access it with minimal configuration. An application developer can achieve these tasks by referring to devices using intuitive names such as /csu/mainCampus/csBuilding/room258/printer/activate. To construct such a name, the developer must make the application aware of the current location. Furthermore, the device must enforce a location-based access control policy to ensure that only users in the same location as the device are allowed to access the device. Our goal is to design a system that leverages the power of names in the Named Data Networking architecture to allow application developers to write code to access and advertise services in a location such as a room or a building. Our system provides a convenient level of indirection so that developers can use names such as /thisRoom/printers/default/activate to initiate a spontaneous interaction with local devices. In this thesis, we describe the system architecture and a prototype implementation. Furthermore, we explore trust and security issues and qualitatively compare our NDN-based solution against an IP-based solution.
Keywords: location awareness; named data networking; spontaneous interaction; location-based services; Internet of things